(untitled) (قضايا سياسية, 2024)
The southern issue in Yemen represents a multiple set of legal, political, economic, military, social and cultural effects and issues that the people of the southern governorates were exposed to after the establishment of Yemeni unity in 1990 between the two countries of Yemen. These demands were discussed at the Yemeni National Dialogue Conference held in 2013 with the participation of representatives of the southern movements and Yemeni political parties. This research explores the contexts in which the southern issue negotiations took place in the Yemeni National Dialogue Conference and analyzes the elements of the negotiating process that were adopted in this context. The current research also seeks to study the patterns of negotiations that characterized the negotiations on the southern issue in the National Dialogue Conference, reveals the negotiation tactics used by the negotiators during the sessions and period of the conference. The results of the current research revealed a diversity of negotiation patterns in the southern issue, between the principled pattern in the first half of the dialogue, and the solid pattern in the second half of the dialogue, which witnessed sharp tensions between the various negotiating parties. The results of the study also revealed that the Yemeni negotiators used many negotiation tactics, especially the fixation tactic, the bogeyman, the specific time, summoning a higher authority, and the exaggerated presentation tactic, whether they used these tactics according to knowledge or spontaneously. The study concluded that the negotiators were able to reach a consensus formula for the southern issue that represents the minimum commonalities between the political parties in Yemen, which was reflected in the final document of the comprehensive National Dialogue Conference, which was signed by most of the political parties participating in the National Dialogue Conference.